Protocol for the development of a core indicator set for reporting burn wound infection in trials: ICon-B study. Issue 5 (14th May 2019) - Davies, Anna; Teare, Louise; Falder, Sian; Coy, Karen; Dumville, Jo C; Collins, Declan; Moore, Luke; Dheansa, Baljit; Jenkins, A Toby A; Booth, Simon; Agha, Riaz; Shah, Mamta; et al.
Abstract : Introduction: Systematic reviews of high-quality randomised controlled trials are necessary to identify effective interventions to impact burn wound infection (BWI) outcomes. Evidence synthesis requires that BWI is reported in a consistent manner. Cochrane reviews investigating interventions for burns report that the indicators used to diagnose BWI are variable or not described, indicating a need to standardise reporting. BWI is complex and diagnosed by clinician judgement, informed by patient-reported symptoms, clinical signs, serum markers of inflammation and bacteria in the wound. Indicators for reporting BWI should be important for diagnosis, frequently observed in patients with BWI and assessed as part of routine healthcare. A minimum (core) set of indicators of BWI, reported consistently, will facilitate evidence synthesis and support clinical decision-making. Aims: The Infection Consensus in Burns study aims to identify a core indicator set for reporting the diagnosis of BWI in research studies. Methods: (1) Evidence review: a systematic review of indicators used in trials and observational studies reporting BWI outcomes to identify a long list of candidate indicators; (2) refinement of the long list into a smaller set of survey questions with an expert steering group; (3) a two-round Delphi survey with 100 multidisciplinary expert stakeholders, to achieve consensus on a short list of indicators; (4) a consensus meeting with expert stakeholders to agree on the BWI core indicator set. Ethics and dissemination: Participants will be recruited through professional bodies, such that ethical approval from the National Health Service (NHS) Health Research Authority (HRA) is not needed. The core indicator set will be disseminated through peer-reviewed publication, co-production with journal editors, research funders and professional bodies, and presentation at national conferences. PROSPERO registration number: CRD42018096647.